Predicting entropy generation in flow of non-Newtonian flow due to a stretching sheet with chemically reactive species. (April 2020) - Khan, Mair; Shahid, Amna; El Shafey, M.; Salahuddin, T.; Khan, Farzana
Highlights: Entropy generation of Williamson nanofuid flow over a stretching surface are investigated. Entropy generation reduced at higher flow is Brinkman number. Entropy generation is also calculated under the effect porous medium. The discretized equation have been solved shooting procedure (Cash and Karp). Abstract: Background: We have studied the steady Darcy Forchheimer MHD generalized non-Newtonian flow of an incompressible non-linear stretched surface in the presence chemical reactive species. Darcy Forchheimer effect and chemically reactive species are considered under entropy generation. Entropy generation analysis has been essentially applied in engineering procedure in order to improve the theoretical and mathematical evaluation problems. Method: To approximate the entropy generation rate, the leading nonlinear equations are solved numerically by using Rung Kutta integration technique with shooting method. Results: Next using the reproduction date, the entropy generation results are discussed by using theoretical and mathematical approaches. The numerical results acquired for different physical mechanism are exposing through graphs and tables. Conclusions: The physical effects of nanomaterials, skin friction coefficient, heat transfer, mass transfer and entropy generation have been illustrated for different values of involved parameters such as the Weissenberg number, magnetic field parameter, porous medium parameter, the Darcy parameter, the Lewis number, thermophoresis diffusion, the Brownian motion parameter, chemical reaction parameter and the Prandtl number. The numerical results acquired for different physical mechanism are exposing through graphs and tables.